Inflammatory response in induced sputum mononuclear cells from patients with acute exacerbation of asthma. Issue 3 (2000) - Hamzaoui, A.; Ben Brahim, M.; Zhioua, A.; Ayed, Kh.; Hamzaoui, K.
Abstract : Examination of sputum provides a direct method to investigate airway inflam mation non-invasively in particular Th1 (IL-2, IFN–γ) and Th2 (IL–4, IL–10) cytokine production. IL–2, IL–4, IL–10 and IFN–γ cytokine were studied in induced sputum mononuclear cells of asthmatic patients. Sputum induction was performed on 10 patients and 10 normal controls. Basal and mitogen-stimulated cytokine production was determined in induced sputum T-cell culture. Supernatants were collected and assayed not only with specific ELISA but also with polymerase chain reaction (PCR) techniques. Data showed a significantly higher production of IL–10 by both the ELISA and the RT-PCR techniques in asthmatic patients compared with sputum mononuclear cells from healthy controls. IL–4 production was detected at a low level using the ELISA method in asthmatic patients. The RT-PCR analysis detected a significantly IL–4-mRNA expression in all asthmatic patients, compared with controls. Results of IL–10 and IL–4 mRNA expression were reproducible. We did not find any alteration in the expression of the type 1 derived cytokines (IL–2 and IFN–γ) in asthmatic patients or in healthy controls. Our study showed a tendency of induced sputum mononuclear cells to express a Th2-like cytokine pattern in acute exacerbation of asthmatic patients, where IL–10 and IL–4 are synthesized in larger amounts. The combination of sputum induction as a non-invasive tool to explore the lung and the identification of disease-associated cytokine expression and of specific cytokine mRNA should help elucidate mechanisms of the immunologically mediated inflammatory responses in asthma.